Identifying Science Content Knowledge of Primary School Pre-Service Teachers at the Essential Physics Concepts - Rifat Shafwatul Anam (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
Science Content Knowledge (SCK) teachers are one of the main things in providing science learning that follows scientific conceptions. One of the causes of misconceptions or inappropriate concepts that students have regarding science is the teacher. So, the purpose of this study is to identify pre-service teachers at primary school about the SCK. The research method used in this study is a quantitative method with a survey design. Data were collected from 131 participants from the Primary School Teacher Education Program in the early semester. The essential concepts in science (physics) used in the study are elementary and junior high school. The instrument is a multiple-choice test with four answers choices with 40 questions. The study finds that for almost every essential physics/science concept, the SCK of the pre-service teachers needs to be improved. This result contradicts our expectations considering the concepts being tested are for elementary and junior high schools. SCK is playing an important element in giving the quality of learning science and building and preparing students to meet the next educational level. Thus, teaching physics from an early age must be taught conceptually and presented with appropriate representations to make it easier for students to learn.